Menelaah Masalah dalam Industri Layanan Warnet dengan Pendekatan Metode Servqual - Azizah Muslimah (Jurnal Strategi Bisnis Teknologi, 2024)
The internet cafe services industry has significant challenges in meeting customer needs and maintaining its competitiveness. This study aims to analyze the problems faced by the internet cafe service industry using the Servqual method approach. This method allows evaluating the quality of services provided by internet cafes along five dimensions: reliability, responsiveness, insurance, empathy and comfort. Data was collected through a survey of internet cafe users and analyzed using statistical techniques. The results of the analysis highlight various problems faced by the internet cafe services industry, and provide valuable insights for industry stakeholders to improve the quality of their services.